Palm oil cultivation in Meghalaya: a health and environmental perspective - Lyngdoh, Markordor; Lyngdoh, Daiahunlang; Sundaram, Shanthosh P. (International Journal Of Community Medicine And Public Health, 2023)
Palm oil cultivation has long been an ongoing controversy in regards to the threat that it poses to the environment. Countries like Indonesia and Malaysia account for the largest share of the world’s palm oil production. The economic benefit that this has bring to these two nations is enormous. However, this is not without consequences. Forests have been destroyed and raging forest fires have claimed the lives of many people. Air and water pollution have threatened the lives of many living beings especially endangered species. Palm oil cultivation also cause occupational health hazards to its many workers. The central government is appealing to many states including Meghalaya to take up palm oil cultivation in order to make the country self-reliant. Many environmentalists are opposed to this move and with good reason. It is therefore imperative to understand the perils of palm oil cultivation in a heavily forested state like Meghalaya not only to the environment but also the health of its citizens as a whole.